EDUKASI MASYARAKAT TERHADAP TANAMAN OBAT TRADISIONAL UNTUK MENINGKATKAN IMUNITAS DI DESA PAKKATTO - Thaha, Salmiyah; Kursia, Sukriani; Rahimah, Sitti; Mashuri, Arif (Arunika: Jurnal Pengabdian Masyarakat, 2022)
The Covid-19 pandemic is still engulfing the world, therefore every individual needs to keep his body's immune system strong so that it is not easy to contract viral diseases. A strong immune system has a very important role in fighting viruses. One way that is taken in an effort to maintain health and maintain and increase immunity is to take traditional medicines to avoid disease attacks, including Covid-19. The purpose of this activity is to provide education on the importance of traditional medicinal plants that are around us to increase the body's immunity. With this educational activity, it will be achieved for people who understand the benefits of traditional medicinal plants as home medicinal plants which are part of herbs that can be used to prevent the corona virus by increasing human immunity.